Economic and technical evaluation of different systems of loquat protected crop - Lorente, Mariano; Orts, José Vicente; Soler, Esteban; Capilla, M. A. (IVIA/CIHEAM, 2023)
The culture of loquat (Eryobotria japonica Lindl.) in the region of "La Marina Baixa" has a substantial social and economic impact. In order to get earlier cropping, different systems of polietylen mesh screens have been introduced. However this cultural practice produced some negative effects, such as the increasing of "purple spot" on the fruits. Appliyng water with microsprinklers reduces the percentage of fruits affected by "purple spot". The high cost of the equipment needed to install the mesh and microsprinklers showed the need of an evaluation and comparison of all systems employed. The results and conclusions are presented in this paper.